Physical Activity Levels and Barriers in Bangladeshi Rheumatoid Arthritis Patients: Insights from a University Hospital (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease that often leads to reduced physical activity, a cornerstone of effective disease management. In Bangladesh, the levels of physical activity and the specific barriers faced by RA patients remain poorly characterized.Objectives: This study aimed to assess the physical activity levels and identify the perceived barriers to physical activity among patients with rheumatoid arthritis in Bangladesh.Methods: A cross-sectional study was conducted among 81 patients with RA at Bangladesh Medical University from October 2021 to September 2022. Data were collected using the Bengali versions of the Global Physical Activity Questionnaire-2 (GPAQ-2) and the Barriers to Being Active Quiz. Disease activity was measured using the Disease Activity Score-28 (DAS-28).Results: The study found that 54.3% of patients engaged in moderate physical activity, 37% had low physical activity, and only 8.7% had high physical activity levels. Common comorbidities included diabetes mellitus (42%) and hypertension (30.9%). A significant negative correlation was observed between disease activity (DAS-28) and physical activity levels (correlation coefficient = -0.384, p < 0.001). The most frequently reported barriers to physical activity were lack of willpower (87.7%), lack of energy (67.9%), and social influence (56.8%).Conclusion: More than one-third of RA patients in this Bangladeshi cohort had low physical activity. The primary barriers were motivational and energy-related, exacerbated by higher disease activity. These findings underscore the urgent need for targeted interventions that address these specific barriers to improve physical activity levels and overall disease outcomes in this population.J Com Med Col Teachers’ Asso July 2025; 29(2): 108-113